Empowerment and Poverty Reduction : A Sourcebook - Narayan, Deepa (Washington, DC: World Bank, 2013)
Poverty will not be reduced on a large scale, without tapping into the energy, skills, and motivation of the millions of poor people around the world. This book offers a framework for empowerment, that focuses on increasing poor people's freedom of choice, and action to shape their own lives. This approach requires three societal changes: a change in the mindset, from viewing poor people as the problem to viewing them as essential partners in reducing poverty; a change in the relationship between poor people, and formal systems, enabling them to participate in decisions that affect their lives; and, a change in formal, and informal institutions to make them more responsive to the needs, and realities of poor people. Based on analysis of experiences from around the world, the book identifies four key elements to support empowerment of poor people: information, inclusions/participation, accountability, and local organizational capacity. This framework is applied to five areas of action to improve development effectiveness. These are: provision of basic services, improved local governance, improved national governance, pro-poor market development, and access to justice, and legal aid. The book also offers tools and practices, focusing on a wide range of topics, to support poor people's empowerment. These range from poor people's enterprises, information and communications technology, and, community driven development, to diagnostic tools such as corruption surveys, and citizen report cards.